Endoscopic treatment of anterior laryngeal web using keel designed from ePTFE followed by voice therapy: a refined technique - Megahed Mohamed Hassan Ahmed; Ahlam Abdel-Salam Nabieh El-Adawy (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Treatment of laryngeal web is challenging due to possibility of recurrence and affected voice quality. Optimal treatment of laryngeal web should emphasize on improving both airway and vocal function. We refined the traditional endoscopic method using a new keel designed from expanded polytetrafluoroethylene (ePTFE) membrane. Our objective is to evaluate the voice outcomes following the endoscopic treatment and voice therapy. Results Ten subjects presented with anterior laryngeal web. Auditory perceptual assessment, stroboscopic examination and acoustic studies were performed pre- and postoperatively. Endoscopic excision of laryngeal web was performed with cold instruments. An individually designed ePTFE keel was fixed by Nylon thread 2–0 at the anterior commissure and tied subcutaneously in the neck. The keel left for 3–5 weeks followed by voice therapy using abdomino-diaphragmatic breathing exercise and relaxation method. Vocal parameters measured were perceptual voice quality using Grade-Roughness-Breathiness-Asthenia-Strain voice scale (GRBAS), stroboscopic score, fundamental frequency (F 0), jitter, shimmer, pitch perturbation question (PPQ), amplitude perturbation question (APQ) and harmonics-to-noise ratio (HNR). Significant decrease in GRBAS (P < 0.001) and significant increase in stroboscopic scores (P < 0.001) were noticed after operation and voice therapy. Also, acoustic voice parameters showed significant improvements. The mean jitter, shimmer, PPQ and APQ showed significant decrease (p = 0.0028, 0.0032, 0.0026, 0.0014, and 0.006 respectively). Overall, 90 % of our subjects have satisfactory voice outcome. Conclusion Endoscopic excision of anterior laryngeal with cold instrument followed by ePTFE keel fixation achieved good long-term voice results. The ePTFE is soft biocompatible material which does not make reaction. The keel should be left in place for sufficient period of time (3–5 weeks). This ensures perfect healing with less or no recurrence. Absence of foreign body reactions in the vocal folds is important for mucosal integrity and good voice outcome. So, the ePTFE could be good alternative for laryngeal keel. Hyperfunctional dysphonia with ventricular hypertrophy may develop in longstanding anterior laryngeal web which needs intensive voice therapy after operation. Our treatment targeted both the organic etiology of dysphonia and the underlying cause of the possible associated functional element of dysphonia.